The effects of pentoxifylline into the kidneys of rats in a model of unilateral hindlimb ischemia/reperfusion injury - Teruya,Roberto (2008)
PURPOSE: To study the role of pentoxifylline (PTX) on remote kidney injury caused by muscle ischemia of left hindlimb of rats. METHODS: After xylazine and ketamine anesthesia, the left hindlimb of rats (n=66) were submitted to 6 hours ischemia (clamping the left common iliac artery). Three groups were used: sham group (SG, n=6), early group (EG, n=30) with reperfusion after 4 hours and late group (LG, n=30) with reperfusion after 24 hours. The saline solution (EG1, n=10 and LG1, n=10) or PTX (40mg.Kg-1) was administered in the reperfusion beginning (EG2, n=10/LG2, n=10) or divided in two doses in the ischemia beginning and reperfusion beginning (EG3, n=10/LG3, n=10). The plasmatic creatinokinase, urea, creatinine, sodium and potassium values were measure and histological samples from left kidney were prepared and H&E stained for scored cellular necrosis and degeneration of kidney tubules and thickness glomerulus determination. The apoptosis index was determined by immunohistochemical expression of the caspase-3. The tests of Mann-Whitney and Kruskal-Wallis (p < 0.05) were applied. RESULTS: The urea (90.5 ± 30.96 mg.dL-1), creatinine (2.28 ± 0.54 mg.dL-1), potassium (16 ± 3.66 mmol.dL-1) and mesangium thickness (0.97 ± 0.42 µm) values were significantly higher in group LG3. There was no significantly difference of caspase 3 expression between EG2 (16.35 ± 1.65%) and LG3 (15.57 ± 2.54%), and both were significantly worse than SG (9.8 ± 1.98%). CONCLUSIONS: The PTX has some protecting effect on remote kidney injury due to hindlimb ischemia/reperfusion injury only in the early phase of reperfusion.